Diagnosis of trichomonas vaginalis in patients with chronic abacterial prostatitis - S. P. Selivanov; Т. А. Kovalik; O. V. Shatohina; S. N. Isayeva (Бюллетень сибирской медицины)
Trichomonasis diagnostics in 326 men with chronic prostatitis was performing. Trichomonas vaginalis was seen in 31,5% and 60,7% together with pyrogenal provocation. Trichomonas vaginalis was detected in 158 (48,5%) by microscopy, in 90 (27,6%) by direct immunofluorescence assay, in 24 (7,4%) by enzyme-linked immunosorbent assay and 6 (1,8%) polymerase chain reaction. Polymerase chain reaction demonstrated lowest sensitiveness.